Binary and ternary new water soluble copper(II) complexes of L-tyrosine and substituted 1,10-phenanthrolines: Effect of substitution on DNA interactions and cytotoxicities - Inci, Duygu; Aydin, Rahmiye; Vatan, Ozgur; Yilmaz, Dilek; Genckal, Hasene Mutlu; Zorlu, Yunus; Cavas, Tolga (Pergamon-Elsevier Science Ltd, 2015)
Binary and ternary water soluble copper(II) complexes - [Cu(nphen)(2)(H2O)](NO3)(2)center dot H2O (1), [Cu(phen)(2)(H2O)](NO3)(2) (2), [Cu(nphen)(L-tyr)(H2O)]NO3 center dot 2H(2)O (3), [Cu(Phen)(tyr)(H2O)] NO3 center dot 2H(2)O (4) - and diquarternary salts of nphen and phen (nphen = 5-nitro-1,10-phenanthroline, phen = 1,10-phenanthroline and tyr = L-tyrosine) have been synthesized and characterized by CHN analysis, H-1 NMR, C-13 NMR and IR spectroscopy, thermal analysis and single crystal X-ray diffraction techniques. The CT-DNA binding properties of these compounds have been investigated by thermal denaturation measurements, absorption and emission spectroscopy. The supercoiled pUC19 plasmid DNA cleavage activity of these compounds has been explored by agarose gel electrophoresis. The cytotoxicity of these compounds against MCF-7, Caco-2, A549 cancer cells and BEAS-2B healthy cells was also studied by using XTT method. The complexes 1-4 exhibit significant high cytotoxicity with low IC50 values in compared with cisplatin. The effect of the substituents of phen and coordinated amino acid in the above complexes are presented and discussed. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Copper(II); 1,10-Phenanthroline; 5-Nitro-1,10-phenanthroline; L-Tyrosine; DNA binding and cleavage; Cytotoxicity